Lidar Application for Mapping and Robot Navigation on Closed Environment - I. Maulana; Angga Rusdinar; R. A. Priramadhi (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2018)
Mapping and navigation on robots are now widely applied in areas such as industry, home appliances, military, exploration and automated vehicles. Mapping and navigation of robots are essential for use in closed environments that are hard to reach by humans. With the mapping and navigation on the robot can allow the robot to recognize the surrounding environment.Data from LIDAR sensors can be converted to maps of the surrounding environment and can be used as an estimate of the position of robots in a closed environment. The distance data from the LIDAR sensor and the LIDAR sensor position status data are converted into Cartesian axes and processed into local maps. Localization using LIDAR sensors are used as a reference to updating global maps.